The impact of covid-19 on the firms’ performance - Ang, Shi Wen; Tan, Nathalie Yi Huang; Lee, Pei Yan; Yow, Ying Yan (2023)
This research has the purpose of examining the impact of COVID-19 on firms’ performance. The explanatory variables include social factor, technological factor, economic factor, and government policies. The theory of resource-based view (RBV) and stakeholder theory will be the fundamental theories of this study to investigate how explanatory variables will affect firms' performance during COVID-19. In this research, primary data as well as a stratified sampling method were implemented. Researchers have developed a questionnaire in order to collect data from respondents. There are two ways researchers collect the questionnaire: exhibitions and Google Forms. In addition to Google Forms, which is regarded as the online collection technique, exhibitions and seminars are regarded as physical collection methods. A total of 507 respondents were collected from small and medium-sized enterprises across Malaysia, with most of the respondents being from Selangor, Kuala Lumpur, Penang, and Johor. Data collected for analysis and interpretation was generated with the aid of IBM SPSS Statistics Version 28. Besides that, descriptive analysis, reliability analysis, multicollinearity tests, and multiple regression analysis were all used to examine and interpret the results. In this research, the result of the reliability test for all variables is excellent, and there is no multicollinearity problem among the independent variables. Based on the research outcomes generated from the multiple regression analysis, social factor, technological factor, economic factor, and government policies had a significant impact on Malaysian small and medium firms’ performance during the COVID-19 pandemic period. In addition, the implications, limitations, and recommendations of the research are also discussed in this study in order to facilitate future research related to this field.